Effect of Bacillus thuringiensis on microbial functional groups in sorghum rhizosphere - Brasil, Carlos; Matsumoto, Leopoldo Sussumu; Nogueira, Marco Antonio; Spago, Flavia Regina; Rampazo, Luís Gustavo; Cruz, Marcio Ferreira; Andrade, Galdino (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to assess the effect of two strains of Bacillus thuringiensis var. kurstaki on sorghum rhizosphere microorganisms. The strains were HD1, that produces the bioinsecticidal protein, and 407, that is a mutant non-producer. The strains do not influence microbial population, but reduce plant growth and improve mycorrhizal colonization and free living fixing N2 community.